Prioritizing Cross-cultural Competence in the 21st Century EFL Classroom: High School Teachers Perspectives and Pedagogical Practices - SLIOUAT, RACHID; BENFILALI, Ismail (International Journal of Linguistics and Translation Studies, 2025)
In today’s interconnected world, cross-cultural competence is a core skill for an individual to be able to navigate diverse cultural landscapes and effectively communicate and collaborate in cross-cultural situations. This study aims to gain insights from High School teachers of English on their perspectives and practices in developing cross-cultural competence among students. It also aims to understand how teachers perceive the importance of these skills, the extent to which they prioritize them in their teaching, and the challenges they face in fostering cross-cultural understanding. For doing this, a mixed methods approach was used to explore teachers’ perspectives, practices and challenges related to developing cross-cultural competence in their classrooms. The study examined 63 high school EFL teachers using a structured online survey with multiple-choice and open-ended questions as an instrument for data collection. The qualitative data were analyzed thematically; whereas the quantitative data were analyzed using the SPSS. Results show that participants view cross-cultural competence as relevant and important for students. The study also explored that understanding cultural differences and similarities is among the top skills teachers intend to develop through discussions and debates. The participants also declared that students’ level and insufficient resources and materials are the main challenges they face in integrating cross-cultural competence in their teaching. Most importantly, it was revealed that teachers are in desperate need of training and textbook updating. These findings provide policymakers with valuable insights to ensure the integration of cross-cultural competence in today’s EFL classes.